Interferon beta treatment is a potent and targeted epigenetic modifier in multiple sclerosis - Xavier, Alexandre; Campagna, Maria Pia; Maltby, Vicki E.; Kilpatrick, Trevor; Taylor, Bruce V.; Butzkueven, Helmut; Ponsonby, Anne-Louise; Scott, Rodney J.; Jokubaitis, Vilija G.; Lea, Rodney A.; Lechner-Scott, Jeannette (Frontiers in Immunology, 2023)
Multiple Sclerosis (MS) has a complex pathophysiology that involves genetic and environmental factors. DNA methylation (DNAm) is one epigenetic mechanism that can reversibly modulate gene expression. Cell specific DNAm changes have been associated with MS, and some MS therapies such as dimethyl fumarate can influence DNAm. Interferon Beta (IFN), was one of the first disease modifying therapies in multiple sclerosis (MS). However, how IFN reduces disease burden in MS is not fully understood and little is known about the precise effect of IFN treatment on methylation. The objective of this study was to determine the changes in DNAm associated with INF use, using methylation arrays and statistical deconvolutions on two separate datasets (total ntreated = 64, nuntreated = 285). We show that IFN treatment in people with MS modifies the methylation profile of interferon response genes in a strong, targeted, and reproducible manner. Using these identified methylation differences, we constructed a methylation treatment score (MTS) that is an accurate discriminator between untreated and treated patients (Area under the curve = 0.83). This MTS is time-sensitive and in consistent with with previously identified IFN treatment therapeutic lag. This suggests that methylation changes are required for treatment efficacy. Overrepresentation analysis found that IFN treatment recruits the endogenous anti-viral molecular machinery. Finally, statistical deconvolution revealed that dendrocytes and regulatory CD4+ T cells were most affected by IFN induced methylation changes. In conclusion, our study shows that IFN treatment is a potent and targeted epigenetic modifier in multiple sclerosis.